Prognostic implications of residual disease tumor-infiltrating lymphocytes and residual cancer burden in triple-negative breast cancer patients after neoadjuvant chemotherapy. (27th December 2018) - Luen, S J; Salgado, R; Dieci, M V; Vingiani, A; Curigliano, G; Gould, R E; Castaneda, C; D'Alfonso, T; Sanchez, J; Cheng, E; Andreopoulou, E; Castillo, M; et al.
Abstract: Background: For primary triple-negative breast cancer (TNBC) treated with neoadjuvant chemotherapy (NAC), higher pretreatment tumor-infiltrating lymphocytes (TILs) correlates with increased pathologic complete response (pCR) rates, and improved survival. We evaluated the added prognostic value of residual disease (RD) TILs to residual cancer burden (RCB) in predicting survival post-NAC. Patients and methods: We combined four TNBC NAC patient cohorts who did not achieve pCR. RD TILs were investigated for associations with recurrence-free survival (RFS), and overall survival (OS) using Cox models with stromal TILs as a continuous variable (per 10% increment). The likelihood ratio test was used to evaluate added prognostic value of RD TILs. Results: A total of 375 RD TNBC samples were evaluable for TILs and RCB. The median age was 50 years, with 62% receiving anthracycline/taxane chemotherapy. The RCB class after NAC was 11%, 50%, and 39% for I, II, and III, respectively. The median RD TIL level was 20% (IQR 10–40). There was a positive correlation between RD TIL levels and CD8+ T-cell density ( ρ = 0.41). TIL levels were significantly lower with increasing post-NAC tumor ( P = 0.005), nodal stage ( P = 0.032), but did not differ by RCB class ( P = 0.84). Higher RD TILs were significantly associated with improved RFS (HR: 0.86; 95% CI 0.79–0.92; P < 0.001), and improved OS (HR: 0.87; 95% CI 0.80–0.94; P < 0.001), and remained significant predictors in multivariate analysis (RFS P = 0.032; OS P = 0.038 for OS). RD TILs added significant prognostic value to multivariate models including RCB class ( P < 0.001 for RFS; P = 0.021 for OS). The positive prognostic effect of RD TILs significantly differed by RCB class for RFS ( P Int =0.003) and OS ( P Int =0.008) with a greater magnitude of positive effect observed for RCB class II than class III. Conclusions: TIL levels in TNBC RD are significantly associated with improved RFS and OS and add further prognostic information to RCB class, particularly in RCB class II.